Potential Aircraft Design Improvement and Sustainability Through Feedback Information - Husain, W M S Wan; Shah, S Aman (International Journal of Engineering and Technology, 2018)
Reflecting on previous case studies, events, research data, and experiences have always been crucial in ensuring the betterment of any working procedure and environment – aircraft maintenance industry included. This paper aims to highlight the importance of having feedback information being constantly disseminated in a swift and effective manner, particularly throughout all levels within the aircraft maintenance industry worldwide – which has been acknowledged by Boeing and subsequently, a few distinguished initiatives such as In Service Data Program (ISDP) and Flight Recorder Data Service (FRDS) have been introduced. In terms of fulfilling aircraft technicians’ needs in their current working environments, such initiatives are crucial for more detailed inspections and supervisions to promote the possibility of enhancement and higher revenues in impending project framework. The trends and behaviour of the previous and/or existing products are analysed and the obtained information will assist appropriate decision-making for future improvements. Commonly, some specific types of information will be collected and thoroughly assessed; these information types include failure types, failure modes and frequencies of failure, and/or replacement and maintenance trends. Overall, feedback information is found to be a major contributor to the sustainability of the aircraft industry.